El capital humano como factor determinante en la calidad de las obras - Córdova Nativí, Edith L. (Revista ALCONPAT, 2012)
Quality Assistance Unit is a Technical Department of Fondo de Conservación Vial (FOVIAL- El Salvador), created in 2007 to monitoring and technical attendance to Quality Control and Quality Assurance to all of FOVIAL maintenance projects. In 2008, according to continuous improvement, Quality Assistance Unit started a pilot program directed toward updating of knowledge, contributing to enrich the technical level of Supervisors and Contractors Companies, who have periodic maintenance contracts of pavement roads. Having obtained very good results in this pilot program, it is decided to extend to all of the FOVIAL projects. This document includes details of the training program and applied researches carried out by FOVIAL and achievements obtained in quality works, through the technical training of human resource. Key words: human resource; training; research; quality